Germanistik im Wandel - Wagner, Doris (Germany, 2025)
Abstract: During 1914‒1925, 26 German prisoners were held in custody in the Turku district prison, awaiting their further fate. How did these prisoners communicate with their Finnishspeaking environment? This question is pursued in this article by examining admission books, court records, registers of foreigners, administrative documents, etc. The data were studied for the period under investigation with special focus on how prisoners communicated effectively The case of the chief cook “Fritz” is particularly interesting because the documents on Fritz are almost complete, from the arrest, including his personal details, to the imprisonment, interrogation and his later release. The case of Fritz describes in detail which stages of detention the prisoners went through before they were released or eventually imprisoned. Of all the prisoners in custody within the selected period, valuable information on the translation and interpreting practice at that time can only be found in the documents relating to Fritz. In his case, a constable was present at the interrogation and acted as an interprete However, he was not paid for this task, as can be seen from the payroll. In my opinion, this is an indication of how little attention was paid to the effective communication between foreign inmates in the Finnish-speaking environment The study period 1914‒1925 was chosen because it includes two important events: World War I and independence of Finland in 1917.
Germanistik im Wandel. Beiträge zur Internationalen Finnischen Germanistentagung 2022 in Oulu